Resilient synchronization of networked robotic systems in adversarial environment - Chen, Hongjian (Nanyang Technological University, 2022)
Over the past few decades, there has been considerable research interest in the field of networked robotic systems. One of research focuses is canonical synchronization issues. The consensus issues investigate how to design a distributed controller so that the networked robots can coordinate with each other to make a common decision. However, in adversarial environments, communication between robots can be disturbed by malicious attacks. The malicious information could be from the external attackers or internal non-participant robots. Considering the widespread use of synchronous algorithms in safety-critical systems, the need for resilient algorithms has attracted a lot of research interest. In this project, a composite resilient synchronization protocol for networked Euler-Lagrange systems is designed with the aid of two existing approaches, “safe kernel” and average sampling interval. The mathematical proof and numerical examples are proposed to verify the feasibility of the protocol. Keywords: Resilient synchronization; Euler-Lagrange Systems; Safe Kernel; Average sampling interval